2011
DOI: 10.1111/j.1364-3703.2011.00750.x
|View full text |Cite
|
Sign up to set email alerts
|

Global changes in gene expression of grapefruit peel tissue in response to the yeast biocontrol agent Metschnikowia fructicola

Abstract: To gain a better understanding of the molecular changes taking place in citrus fruit tissue following the application of the yeast biocontrol agent Metschnikowia fructicola, microarray analysis was performed on grapefruit surface wounds using an Affymetrix Citrus GeneChip. Using a cut-off of P < 0.05 and a 1.5-fold change difference as biologically significant, the data indicated that 1007 putative unigenes showed significant expression changes following wounding and yeast application relative to wounded contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 48 publications
0
56
0
1
Order By: Relevance
“…The antagonistic yeasts may serve as an elicitor, triggering ROS signaling in host tissue and leading to the activation of host defenses (52)(53)(54). This premise is supported by studies analyzing gene/protein expression during yeast-fruit interactions (20,55,56). A proteomic analysis indicated that an antagonistic yeast, P. membranaefaciens, induced six antioxidant proteins in peach fruit, including catalase, glutathione peroxidase, and peroxiredoxin.…”
Section: Environmental Stressesmentioning
confidence: 94%
“…The antagonistic yeasts may serve as an elicitor, triggering ROS signaling in host tissue and leading to the activation of host defenses (52)(53)(54). This premise is supported by studies analyzing gene/protein expression during yeast-fruit interactions (20,55,56). A proteomic analysis indicated that an antagonistic yeast, P. membranaefaciens, induced six antioxidant proteins in peach fruit, including catalase, glutathione peroxidase, and peroxiredoxin.…”
Section: Environmental Stressesmentioning
confidence: 94%
“…Previous transcriptome studies of Citrus fruit peel and peel sections were designed to investigate stress and defense responses but did not provide direct insights into essential oil biosynthesis (Maul et al, 2008;González-Candelas et al, 2010;Matas et al, 2010;Ballester et al, 2011;Hershkovitz et al, 2012). We optimized a protocol for the collection of intact ECs from the flavedo layer of grapefruit peel by laser microdissection and pressure catapulting, subsequent isolation of RNA, and linear amplification of transcripts for analysis on Affymetrix Citrus genome oligonucleotide microarrays.…”
Section: Analysis Of Global Transcript Expression Patterns In Ecs Surmentioning
confidence: 99%
“…For example, transcripts related to terpenoid synthases, which catalyze the first committed step in the biosynthesis of terpenoid essential oil constituents, were highly expressed in Citrus fruit peel when compared with other tissues and organs Dornelas and Mazzafera, 2007;Takita et al, 2007). More recently, genome-wide oligonucleotide microarray analyses have been conducted with Citrus peel tissue (Maul et al, 2008;González-Candelas et al, 2010;Matas et al, 2010;Ballester et al, 2011;Hershkovitz et al, 2012). However, these studies were aimed at evaluating specific developmental processes or stress/ defense responses of Citrus and did not provide direct insights into peel essential oil biosynthesis.…”
mentioning
confidence: 99%
“…Developments in deep sequencing, transcriptomics, MS-MS proteomics, metagenomics, comparative and functional genomics can be utilized to determine changes in the physiological status of biocontrol agents, and the effect of environmental stress on its intracellular machinery (Hershkovitz et al, 2011;Hershkovitz et al, 2013;Sui et al, 2015). Changes in the level of expression of "biocontrol genes" during mass production, formulation and storage, or in response to exposure and contact with host plant tissue after application can now be more readily investigated.…”
Section: Mechanisms Of Action Involved In Biocontrol Systemsmentioning
confidence: 99%